Computer Integrated Manufacturing of Polyurethane Foams Steered by Measured and Calculated Data in Comparison - Horacek, Heinrich (Journal of Research Updates in Polymer Science, 2016)
Polyurethane foams were manufactured under continuous measurements of isocyanate content, temperature, expansion and viscosity. Parallel model calculations were executed based on the driving force of 50kJ/mole heat of reaction of the energy rich isocyanate group and on thermodynamic balances of weight and heat of formation as well as on a kinetic model using a first order reaction for the isocyanate consumption and a relation for the viscosity dependent on conversion and on a viscosity constant. The agreement between continuous measured and calculated data was satisfying. The parameters isocyanate content, temperature, expansion and viscosity controlled and steered the variables of the production plant, like dosage of components, temperature and conveyer speed. The kinetic model was also valid for polyurethane foams with additives, which did not react with components of foam, like flame retardants or pigments. The thermodynamic balances of weight and heat predicted residues and consumed heats by degradation under fire, which correlated with those measured by TGA and DSC. The target was to establish computer integrated manufacturing without continuous measurements but by mere model calculation. This was possible with the knowledge of the first order velocity constant and the viscosity constant.